Community health model to manage health hazards related to Mount Cameroon eruptions in West Africa - Atanga, Mary Bi Suh (University of the Free State, 2010)
Mount Cameroon is one of Africa’s largest and most active volcanoes, the last eruption occurring in 1999-2000. Communities in close proximity to this mountain were and could again be adversely affected by such volcanic eruptions. The goal of the study was to develop a community health adaptable model for the management of health care related hazards – not only for this community, but also for others within Cameroon and Africa. An exploratory qualitative approach to data collection and analysis was used in order to gain insight into what would be acceptable to the community. Purposive sampling was used to identify three groups of community members and a group of health care workers who have lived through a previous eruption (who turned out to be nurses and nurses’ aids only). Data was transcribed, notes made among researcher and assistants and cross-matched to arrive at occurring themes. The significance attached to the mountain and its eruptions, management strategies from the perspective of the community members and an identification of what matters most in this regard were elicited. An analysis of documented evidence from local resources focused on the realities of such a hazard, prevention and mitigation measures, as well as adaptable methods that could inform the model. The exploration of international relevant strategies in managing natural disasters in general, and volcanic disasters in particular, as well as a literature review, was conducted. The findings were triangulated to inform the development of an adaptable model. After an exploratory pilot study (pretest), using members of another community that was affected to some extent during the 1999-2000 eruption, two participant focus group discussions were held with each of three groups of community members. These included a group of elders, men and women. The findings indicated that community members regarded the mountain as a god to be appeased. Thus, some of the cultural practices exposed the community even further to hazards related to a volcanic eruption. They emphasised the protection of women and children, had some traditional health care actions in place, respected the local council for its important role, but thought that their role was marred by limitations such as infrastructure and resources. They were concerned about any evacuation process and confirmed previous negative experiences in this regard. Focus group discussions with a group of health workers indicated a slightly more scientific view of the eruptions and emphasised the livelihood value of the fertile soil surrounding the mountain. The group expressed concerns regarding cultural practices and the severe lack of health care infrastructure and resources, and expressed limited management strategies to deal with a health hazard of such magnitude. Documented evidence and literature was limited, but it was found that within Africa, concerns were similar. Management strategies were linked to a number of government departments’ involvement and scientific research and monitoring done by academic institutions or other facilities. Internationally, a number of directive frameworks exist but the need for an in-country framework, incorporating the needs of local communities, is emphasised in some models and approaches. Triangulation of focus group results, and an analysis of local and national documented evidence and international literature, indicated that a critical need exists to focus on the community’s intricate relationship with the mountain (inclusive of cultural and religious practices), the involvement of community members as critical role-players, the enhancement of health care services, the development of the knowledge and skills of health care workers, and addressing or even simplifying the complex nature and directives on national level to deal with such emergency situations. These five major focus areas form the basic tenets of a community adaptable model that values being, belonging and becoming. In this way, community members are active participants in assessment, planning, implementation and evaluation.
Thesis (Ph.D. (Nursing))--University of the Free State, 2010
Keywords: Community health nursing; Volcanoes -- Cameroon -- Cameroon Mountain; Disaster relief -- Cameroon -- Cameroon Mountain